The "nugget design": A modified segmental gracilis free flap for small-sized defect reconstruction on the lower extremity. Issue 9 (September 2017) - Tremp, M.; Oranges, C.M.; Wang, W.J.; Wettstein, R.; Zhang, Y.X.; Schaefer, D.J.; Kalbermatten, D.F.
Summary: Background: Little attention has been given to the segmental free gracilis muscle flap supplied by secondary proximal pedicles. We introduce a technical refinement for small-sized three-dimensional defect reconstruction on the foot. Methods: Between November 2013 and August 2016, three patients with a mean age of 66 years (range 47–70 years) were included. A segmental gracilis free flap supplied by the most proximal secondary pedicle was harvested according to a modified "nugget design" to treat small-sized defects on the lower extremity requiring dead space reconstruction. Minor and major complications, sensitivity with Semmes-Weinstein monofilament test, soft tissue stability and patient satisfaction at final follow-up were recorded. Results: In one case, a segmental gracilis muscle was used for dorsal foot reconstruction after debridement of metatarsal phalanx I with osteomyelitis. In two cases, the segmental gracilis free muscle was harvested for defect reconstruction on the right plantar foot after excision of a melanoma. The first patient required revision after partial failure of the initial segmental gracilis free muscle flap. Overall, good results in foot function and a high degree of patient satisfaction was achieved (Likert scale 9.7, range 9–10) after a mean follow-up of 13 months (range 3–24 months). Conclusions: Taken from the very proximal dorsal part of the gracilis muscle supplied by the most proximal secondary pedicle and leaving the vast majority of the muscle intact preserves the option to harvest a normal gracilis flap. This technique is especially suitable for small, three-dimensional defects on the lower extremity.